CEO Busyness and Earnings Management: Evidence from Non-financial Companies listed in Indonesian Stock Exchange - Zakiya, Fudhla; Arifin, Taufiq (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2024)
This study examines the impact of CEO's busyness on earnings management. The samples are 595 non-financial companies Indonesian listed in Stock Exchange from 2015 to 2020 (2,757 observations). Using OLS regression, the results of this study revealed that companies with CEO's busyness has a positive significant influence on earnings management. The results also show that companies whose CEOs also serving as a board of commissioners in another company (CEO duality) tend to have smaller level of earnings management. This study also uncovered that CEOs attendance in board meetings has no moderating effect on the positive influence of CEO busyness on earnings management. The results are robust as propensity score matching and entropy balancing tests have been conducted.